WASTE REDUCTION IN BRAKE LINING PRODUCTS TYPE 51 HS USING LEAN SIX SIGMA METHOD - Saryatmo, Mohammad Agung; Wongkar, Joshua Ricardo; Kristina, Helena Juliana; Andres (Jurnal Ilmiah Teknik Industri, 2023)
Every company desires a profit, and its production system must continually develop and become more productive. Companies can boost their production productivity in a variety of ways, including by enhancing their production process system and removing impediments. This research was conducted at a company in Tangerang that specialized in manufacturing brake linings. On the basis of the results of field research, manufacturing department defects and inventory have been detected. The research phases employ the DMAIC model. The define phase employs SIPOC and CTQ diagrams. Using WAM to identify waste that happens through the distribution of questionnaires during the measurement phase. According to the measure stage's calculation, the company's current efficiency level is 26.85 percent. The DPMO value is 6,222.71 and sigma number indicates a quality level of 4.91. After learning the company's status, the research continued with an FMEA examination of the root cause. On the basis of the results of the analysis, proposals for changes to the brake linings production steps were made. The research was continued in the third phase, known as control, which consisted of recalculating the company's status after the implementation of modifications. The calculation findings demonstrate an increase in process cycle efficiency to 35.33 percent. In addition, a reduction in the value of faults per million opportunities resulted in the production of 4,524.88 products and an increase in the sigma level to 5.12. This demonstrates a gain in efficiency of 8.48%, a drop-in DPMO of 1,697.83 products, and a 0.21 increase in sigma value.